Design Flaws: Consequences of the Coverage Gap in Food Programs for Children at Kindergarten Entry. (21st May 2018) - Arteaga, Irma; Heflin, Colleen; Parsons, Sarah
Abstract: Children age out of the Women, Infants, and Children (WIC) program at 60 months and become eligible for the National School Lunch Program (NSLP) upon kindergarten entry. During this period of time, low‐income children experience fewer food support services than at any other time. Using the Early Childhood Longitudinal Study, we examine the effects of the duration of the coverage gap between WIC and NSLP on kindergarteners' skills. Results show evidence of negative effects on reading, though not on math. Findings also suggest that, for children in full‐day kindergarten, effects on reading fade out in the spring term.